Side effects may vary - Murphy, Julie, 1985- (Balzer + Bray, an imprint of HarperCollinsPublishers, 2020)
"Alice is ready to go out in a blaze of glory, but then she discovers she's in remission from cancer and she must deal with all of the mistakes she's made and the people she's hurt"--